2010
DOI: 10.1063/1.3295707
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic noise in MgO-based magnetic tunnel junction rings

Abstract: Magnetization switching is investigated in ring-shaped MgO-based magnetic tunnel junctions with 168% tunneling magnetoresistance. Besides the forward and reverse onion states, two vortex states and several metastable states are observed for the ferromagnetic free layer. Electrical noise is used to characterize the low frequency magnetization dynamics; a stationary 1 / f noise spectrum is observed within each magnetic state but they are separated by noise peaks which show a 1 / f 2 spectrum that is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The linear dependence has been previously reported in AlO x and MgO MTJs. 9,10,19,[23][24][25] With their lower field sensitivity values ( 1%=mT), the yoke-shaped GMR sensor shows the lowest magnetic noise level. But from the applications point of view, low field sensitivity is not what is needed for a sensor.…”
mentioning
confidence: 99%
“…The linear dependence has been previously reported in AlO x and MgO MTJs. 9,10,19,[23][24][25] With their lower field sensitivity values ( 1%=mT), the yoke-shaped GMR sensor shows the lowest magnetic noise level. But from the applications point of view, low field sensitivity is not what is needed for a sensor.…”
mentioning
confidence: 99%
“…3,4 Normally, thermal domain hoppings are connected with the magnetization rotations or fluctuations in a complicated internal anisotropic field due to shape, stress, impurity, displacement, nonuniformity, and other factors. 3,5 In theory, magnetic hysteresis and 1/f resistance noise can be suppressed by meliorating the internal anisotropic field of ferromagnetic layers in MR sensors. It was recently demonstrated that the magnetic hysteresis and 1/f resistance noise of MgO tunneling MR sensors was improved by properly thinning their ferromagnetic layers with the enhancement of perpendicular anisotropic field but the expense of large sensitivity drop.…”
mentioning
confidence: 99%
“…Further details on the sample growth process and measurement can be found in Refs. [20][21][22]. Figure 1 shows MR curves for an EB-MTJ and a rf-MTJ.…”
mentioning
confidence: 99%